Multimodalitas Bahasa Satire Dengan Bentuk Komodifikasi Pada Program Lapor Pak Trans7 dan Main Hakim Sendiri NET.TV - Amalia, Yasinka; Sudarsono, Achmad Budiman; Olivia, Helen; Marta, Rustono Farady; Sarasati, Fitri (Jurnal Politikom Indonesiana, 2024)
Abstract The development of television in the digital era has now encouraged the media industry to produce content that is not only entertaining but also has economic value. One of them is the concept of satire in television programs. Satire in the program “Lapor Pak!” on Trans7 and “Main Hakim Sendiri” on NET.TV is a creative form conveying social criticism. This research aims to analyse the form of commodification and satire language style used in the program “Lapor Pak! Najwa Shihab Episode” and “Main Hakim Sendiri bribery episode”. This research is qualitative with the method od multimodality analysis by John Bateman, and theory used is the political economy of media by Vincent Mosco to explain the form of commodification and the theory of language style by Holbert to identify the type of satire used in the two programs. The results showed that Content Commodification – Horatian Satire (KK/SH) was the highest frequency with 9 data and Conetnt Commodification - Juvenalian Satire (KK/SJ) was the second highestfrequency element with 6 data used in the program “Lapor Pak!”. while in the program “Main Hakim Sendiri”, the highest frequency is shown in 3 data containing the element of Content Commodification – Horatian Satire (KK/SH) and 1 data containing the element of Audience Commodification – Juvenalian Satire (KA.SJ). The determination of data is done by categorizing dan elaborating on scenes that show elements of commodification and elements of satirical language. Keywords: Satirical Language, Commodification, Multimodality